Pyridoxamine Supplementation Effectively Reverses the Abnormal Phenotypes of Zebrafish Larvae With PNPO Deficiency - Chen, Po-Yuan; Tu, Hung-Chi; Schirch, Verne; Safo, Martin K.; Fu, Tzu-Fun (Frontiers in Pharmacology, 2019)
Neonatal Epileptic Encephalopathy (NEE), as a result of pyridoxine 5’-phosphate oxidase (PNPO) deficiency, is a rare neural disorder characterized by intractable seizures, and usually leads to early infant death. The clinical phenotypes do not respond to antiepileptic drugs, but are alleviated in most cases by giving large doses of pyridoxal 5’-phsophate (PLP). PLP is the active form of vitamin B6 participating in more than 100 enzymatic pathways. One of the causes of NEE is pathogenic mutations in the gene for human PNPO (hPNPO). PNPO is a key enzyme in converting pyridoxine (PN), the common dietary form of vitamin B6, and some other B6 vitamers to PLP. More than 25 different mutations in hPNPO, which result in reduced catalytic activity, have been described for PNPO-deficiency NEE. To date, no animal model is available to test new therapeutic strategies. In this report, we describe using zebrafish with reduced activity of Pnpo as an animal model. Knocking down zPnpo resulted in developmental anomalies including brain malformation, and impaired locomotor activity, similar to the clinical features of PNPO-deficiency NEE. Other anomalies include a defective circulation system. These anomalies were significantly alleviated by co-injecting either zpnpo or hPNPO mRNAs. As expected from clinical observations in humans, supplementing with PLP improved the morphological and behavior anomalies. PN only showed marginal positive effects, and only in a few anomalies. Remarkably, pyridoxamine (PM), another dietary form of vitamin B6, showed rescue effects even at a lower concentration than PLP, presenting a possible new therapeutic treatment for PNPO-deficiency NEE. Finally, GABA, a neurotransmitter whose biosynthesis depends on a PLP-dependent enzyme, showed some positive recue effect. These results suggest zebrafish to be a promising PNPO-deficiency model for studying PLP homeostasis and drug therapy in vivo.